2014
DOI: 10.21071/az.v63i243.529
|View full text |Cite
|
Sign up to set email alerts
|

Parámetros genéticos para caracteres productivos y reproductivos en Holstein y Jersey Colombiano

Abstract: El objetivo de este estudio fue estimar parámetros genéticos y fenotípicos en características productivas y reproductivas en ganado Holstein y Jersey de Antioquia, Colombia. La información fue obtenida de 85 hatos lecheros de raza Holstein y 7 hatos de raza Jersey, ubicados en 18 municipios del Departamento de Antioquia. Las características productivas evaluadas fueron: producción de leche (PL), porcentaje de proteína (PP), porcentaje de grasa (PG) y puntaje de células somáticas (SCS) y las características rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Results of Jersey herds from Colombia, reported by Rincón et al (2015) (P% = 3.44% and F% = 4.66%) and Zambrano et al (2014) (P% = 3.44% and F% = 4.71%) were also similar to those of the present study. In addition, our average value for SCS (5.9) was close to the value estimated by Missanjo et al (2013) for Jersey in Zimbabwe (5.54) and higher than the values reported by Zambrano et al (2014) prominent position in the world rank of milk production, the productivity of Jersey herd in Brazil is more similar to that in underdeveloped countries such as Zimbabwe and Colombia, compared with that in developed countries such as USA. This result indicates the need to implement Jersey breeding programs that lead to the selection of animals based on estimated genetic breeding values.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Results of Jersey herds from Colombia, reported by Rincón et al (2015) (P% = 3.44% and F% = 4.66%) and Zambrano et al (2014) (P% = 3.44% and F% = 4.71%) were also similar to those of the present study. In addition, our average value for SCS (5.9) was close to the value estimated by Missanjo et al (2013) for Jersey in Zimbabwe (5.54) and higher than the values reported by Zambrano et al (2014) prominent position in the world rank of milk production, the productivity of Jersey herd in Brazil is more similar to that in underdeveloped countries such as Zimbabwe and Colombia, compared with that in developed countries such as USA. This result indicates the need to implement Jersey breeding programs that lead to the selection of animals based on estimated genetic breeding values.…”
Section: Discussionsupporting
confidence: 69%
“…In previous studies carried out with the Jersey breed in other countries (Sharma et al, 1983;Missanjo et al, 2013;Rincón et al, 2015;Zambrano et al, 2014) estimates of heritability for MY ranging from low to moderate were found. The value found in the present study (0.16±0.02) was similar to those reported by Sharma et al (1983) and Rincón et al (2015), who found the heritability for MY in the Jersey breed of 0.14 and 0.15, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Valores similares reporta (Zambrano et al, 2014), en donde indica que las correlaciones fenotípicas fueron bajas, ya que variaron entre -0,17 y 0, 16. Los animales de raza Holstein presentan un mayor volumen de producción respecto a los Pardo Suizo y Jersey, en correspondencia con los resultados presentados por (Zambrano et al, 2013), (Ríos-Utrera et al, 2015.…”
Section: Dprunclassified